Carcinoid tumors: Tumores carcinoides del aparato digestivoMESA REDONDA Realizada en la sesión conjunta de la Sociedad de Cirugía del Uruguay y la Sociedad de Anatomía Patológica del Uruguay, el 8 de octubre de, 1975 - D'Auria, Agustín; Reissenweber, Nelson; Estrugo, Roberto; Cassinelli, Daniel; Gardiol, Valdo; Perdomo, Roberto; Bonifacio, Juan; Acosta Ferreira, Walter; de los Santos, Julio; Bonaba, Roberto; et al. (Cirugía del Uruguay, 1977)
The idea of this round table is to show sorne particularities with resulting special biological behaviour of these tumors.